Kebijakan Model Crime Prevention Through Social Development Dalam Penanggulangan Tindak Pidana Terorisme - Dwi Nurahman; Dina Haryati Sukardi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
The problem in this study is how the implementation of the conception of Crime Prevention Through Social Development (CPTSD) by Bhabinkamtibmas in combating criminal acts of terrorism and why there are obstacles to the implementation of the conception of CPTSD by Bhabinkamtibmas in combating criminal acts of terrorism. The research method specifically uses this type of qualitative research with a normative juridical approach to the problem and an empirical approach. The types of data used are primary data and secondary data. Primary data were obtained from interviews with resource persons and secondary data from literature studies. The results of the study indicate that the CPTSD model policy by Bhabinkamtibmas in overcoming criminal acts of terrorism is carried out through preventive, preemptive, and repressive efforts. Preventive efforts are supervision of chemicals that can be processed into explosives. Preemptive efforts are holding tabligh akbar and re-instilling Pancasila values ​​in society. The repressive effort is the establishment of the Anti-Terror Task Force. The obstacle in implementing the CPTSD model policy by Bhabinkamtibmas in overcoming criminal acts of terrorism is that Bhabinkamtibmas still lacks resources both in terms of quantity of members and in the field of facilities and infrastructure which includes the number of vehicles and task tools used to carry out Anjau Glare and binluh to the community. The Binmas Pioneer program through the CPTSD by Bhabinkamtibmas has not yet reached the target, so it has not been maximal in raising public awareness and preventing crime.